A Survey of Biology Alternative Conceptions among General Education Students in the Sultanate of Oman - Abdullah Kh. Ambusaidi; Suliaman M. Al-Balushi; Saif Al-Hiji; Ali H. Al- Shuaili (Sultan Qaboos University, 2014)
This study aimed at investigating Omani general education alternative conceptions in some biological concepts. To achieve this aim, a two-tier MCQs biology test, consisting of 40 items, was constructed. The test was verified by a panel of experts in science teaching to check its validity, whereas the reliability was calculated using Cronbach alpha for internal consistency. Alpha value was 0.85. The test was administered to 1013 students, randomly selected from four educational governorates in the Sultanate of Oman in the 2010/2011 school year. The results of the study showed that Omani general education students held several alternative conceptions in all four domains of the biology: systems and life processes, reproduction and heredity, cell and its functions and diversity and adaptation. Accordingly, the study proposed several recommendations based on the results.